The Ability of Soil Candida albicans Secreted Potential Protease and Lipase - Ririn Puspadewi; Putranti Adirestuti; Mira Andam Dewi; Wakilatul Hasanah (Biota, 2020)
Candida spp secreted a different kind of extracellular enzymes. Protease and lipase are the enzymes that are commonly used in the food and pharmaceutical industries. This study aimed to examine protease and lipase activity of Candida tropicalis isolated from the soil of the Medicinal Plant Garden of the Faculty of Pharmacy, Universitas Jenderal Achmad Yani, Indonesia. Candida isolate was subjected to the fermentation process to obtain bioactive metabolites. The result was analyzed using ANOVA within a 5% interval of confidence, continuing with PostHoc. The result showed the Candida tropicalis metabolite giving the best proteolytic index value (0,6556 ± 0,0090) U/mL. The metabolite isolate of Candida tropicalis had the highest activity, amounting to 5,776 ± 0,495 U/mL. The best results of lipolytic index value (0,394 ± 0,053) U/mL. The Candida tropicalis metabolites produced the highest lipase enzyme after nine days of fermentation in 5.2917±0,0167 U/mL.